Mengintegrasikan Keterampilan Kepemimpinan ke dalam Kurikulum Akuntansi : Persepsi Stakeholders dan Pengujian Model Pembelajaran Kooperatif - Mayar Afriyenti; Fauzan Misra (Jurnal Riset Akuntansi Terpadu, 2019)
This study examines the perception of stakeholders (students, lecturers and practitioners) about skills that must be possessed by the students,the feasibility of the accounting curriculum in the development of such skills, and to tests the effectiveness of cooperative learning model in developing leadership skills.To accomplishh this purpose, two studies were conducted. Study 1 investigates the perception of three different parties of stakeholders regarding leadership skills, while the second study tests the effectiveness of cooperative learning model.  Study 1 was conducted by a survey approach while study 2 was conducted through a simulation of cooperative learning. Data from study 1 was analyzed using chi-square test while data from study 2 analyzed with a descriptive statistics and a t-test. The result of study 1 showed that there is no significant differences in perception between students and lecturer regarding the provisions given to fulfill the needs of the workforce, and there is a shared belief between students and employers about the adequacy of the accounting curriculum in developing leadership skill and the attributes of the main skills that must be possessed by the students. Meanwhile, the results of study 2 showed the effectiveness of cooperative learning model in developing student’s leadership skills.